EFEKTIVITAS TEORI PURCHASING POWER PARITY PADA NILAI TUKAR RUPIAH TERHADAP DOLLAR AS - , Diwayana Putri Nasution (Jurnal Kajian Ekonomi dan Kebijakan Publik (JEpa); Vol 2 No 1 (2017): JURNAL Kajian Ekonomi dan Kebijakan Publik, 2018)
This study entitled "Identification of the barriers in the development of small businesses (studies in the restaurant business in Medan)". The aim of this study was to determine the barriers that occurs in the restaurant business in the City Medan. Variabel studied were barriers to enterprise development as the dependent variable, and the difficulty of access to capital and price competition are not as competitive as the independent variable. The research looked at the effect of the independent variable is the difficulty of access to capital and price competition are not competitive on the dependent variable, namely the obstacles of business development. The hypothesis of this study indicate that the difficulty of access to capital and price competition are not as competitive have a positive and significant impact on the variable barriers to the development of the restaurant business in the city of Medan. Research used data croos section by taking a sample was 50 restaurant business. Data analysis method used is the Least Squares Method (Ordinary Least Squared) in estimating the results of his research. In this study, using the Test of Goodnest of Fit to see the value of the coefficient of determination, t test and f test. Testing irregularities classic assumption by looking at whether there is multicollinearity and heteroscedasticity.